Environmental Innovation: in search of a meaning - Angelo, Fernanda Dias; Jabbour, Charbel José Chiappetta [UNESP]; Galina, Simone Vasconcelos Ribeiro (Emerald, 2012)
The purpose of this paper is to propose a definition of the term “green/environmental innovation”, based on a systematic literature review. Design/methodology/approach– The literature review conducted in this research was based on papers published in ISI Web of Science and Scopus databases. Findings– Environmental innovations are organizational implementations and changes focusing on the environment, with implications for companies’ products, manufacturing processes and marketing, with different degrees of novelty. They can be merely incremental improvements that intensify the performance of something that already exists, or radical ones that promote something completely unprecedented, where the main objective is to reduce the company's environmental impacts. In addition, environmental innovation has a bilateral relationship with the level of proactive environmental management adopted by companies. Increasing of environmental innovation tends to come up against many barriers.
Keywords: Organizational culture; Governance; Ethos; Environmental management; Green innovation; Eco-innovation; Literature review